2013
DOI: 10.1016/j.jhep.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid transporters and regulatory nuclear receptors in the liver and beyond

Abstract: SummaryBile acid (BA) transporters are critical for maintenance of the enterohepatic BA circulation where BAs exert their multiple physiological functions including stimulation of bile flow, intestinal absorption of lipophilic nutrients, solubilization and excretion of cholesterol, as well as antimicrobial and metabolic effects. Tight regulation of BA transporters via nuclear receptors is necessary to maintain proper BA homeostasis. Hereditary and acquired defects of BA transporters are involved in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
273
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(286 citation statements)
references
References 161 publications
(146 reference statements)
11
273
0
2
Order By: Relevance
“…Gadoxetic acid enters the hepatocytes via active transport by OATP1B1/3 and is excreted into the biliary tree via MRP2 (23,28). Organic acid efflux from hepatocytes may also occur through the sinusoidal membrane because of bidirectional transport with OATP1B1/3 and MRP3 (23,28). We found that OATP1B1/3 expression was the main determinant responsible for uptake of gadoxetic acid in HCAs (P , .001).…”
Section: Gastrointestinal Imaging: Hepatocellular Adenoma With Gadoxementioning
confidence: 75%
See 1 more Smart Citation
“…Gadoxetic acid enters the hepatocytes via active transport by OATP1B1/3 and is excreted into the biliary tree via MRP2 (23,28). Organic acid efflux from hepatocytes may also occur through the sinusoidal membrane because of bidirectional transport with OATP1B1/3 and MRP3 (23,28). We found that OATP1B1/3 expression was the main determinant responsible for uptake of gadoxetic acid in HCAs (P , .001).…”
Section: Gastrointestinal Imaging: Hepatocellular Adenoma With Gadoxementioning
confidence: 75%
“…It is well known that gadoxetic acid movement in hepatocytes is mediated by various transporters located on either the sinusoidal (OATP1B1/3 and MRP3) or canalicular (MRP2) membranes of the cell (19,22,32). Gadoxetic acid enters the hepatocytes via active transport by OATP1B1/3 and is excreted into the biliary tree via MRP2 (23,28). Organic acid efflux from hepatocytes may also occur through the sinusoidal membrane because of bidirectional transport with OATP1B1/3 and MRP3 (23,28).…”
Section: Gastrointestinal Imaging: Hepatocellular Adenoma With Gadoxementioning
confidence: 99%
“…Bile acid transporters, namely, BSEP, NTCP, and MRP 2 , play a key role in bile acid homeostasis (39,40), while inhibition of the bile acid transporters BSEP and NTCP was suggested to participate in INH-induced liver injury pathogenesis (41). Our preceding study (22) showed that the INH-LPS combination elevated the expression of the bile acid-synthesizing enzyme (CYP7A1) while the expression of transporters (BSEP, NTCP, and MRP 2 ) was significantly reduced.…”
Section: Discussionmentioning
confidence: 95%
“…FXR agonism increases BSEP, MRP2, and OST expression and represses NTCP and OATP expression in hepatocytes. CAR or PXR agonism increases OATP, SULT2A1, MRP2, MRP3, and MRP4 expression (Xie et al, 2001;Stahl et al, 2008;Halilbasic et al, 2013). The net effect of this NHR interplay, and its modulation by members of the BA pool, is increased efflux of BAs out of the hepatocyte, as well as shunting of BAs toward MRPs, especially after sulfation to 3-O-sulfates that are excreted in the urine (Van Berge Henegouwen et al, 1976;Keppler, 2011;Humbert et al, 2012).…”
Section: Mechanisms Leading To Drug-induced Cholestasis 569mentioning
confidence: 99%